Factors Associated With the Utilisation and Unmet Need for Modern Contraceptives Among Urban Women in Kenya: A Cross-Sectional Study - Akoth, Catherine; Oguta, James Odhiambo; Kyololo, O'Brien M.; Nyamu, Martin; Ndirangu, Michael Ndung'u; Gatimu, Samwel Maina (Frontiers in Global Women's Health, 2021)
Background: Family planning (FP) is a key intervention in improving maternal and child health. Hence, we assessed the factors associated with utilisation and unmet need for modern contraceptives among urban women in Kenya. Methods: The study used pooled data on 10,474 women 15–49 years from the seven rounds of the performance monitoring for accountability surveys collected between 2014 and 2018. The surveys were conducted in 11 of the 47 counties of Kenya using a multistage cluster design. Sample characteristics were described using frequencies and percentages while factors associated with utilisation and unmet need for modern contraceptives were assessed using multivariable logistic regressions. Results: The prevalence of modern contraceptives use and unmet need for FP among urban women in Kenya was 53.7% [95% confidence interval (CI) 52.1–55.3%] and 16.9% (15.8–18.1%), respectively. The use of modern contraceptive was associated with the county of residence, age, marital status, parity, education, household wealth quintile, exposure to media, and survey year. Teenagers, poorest urban women, women with no formal or primary level of education and those who seek services at a dispensary or health centres had higher odds of unmet need for FP while women who resided in Kitui and Nyamira counties had reduced odds of unmet need for FP. The odds of unmet need decreased with the survey year while that of modern contraceptive use had an inverse trend. Conclusion: Overall modern contraceptive use in urban areas is lower than the national average while the unmet need for FP is higher than national average, highlighting a potential urban-rural disparity in FP indicators in Kenya. Individual sociodemographic and socioeconomic and contextual factors are associated with the use of modern contraceptive and unmet need for FP among urban women in Kenya. Urban family planning policies and programmes in Kenya need to focus on strengthening urban healthcare systems to provide equal and accessible FP services, especially targeted towards teenagers and young women and those of low socioeconomic status.